Analytical prediction of thermophysical properties of fluids embedded with nanostructured materials. (24th March 2008) - Vasu, V.; Krishna, K. Rama; Kumar, A.C.S.
Nanofluids are new class of heat transfer fluids developed by suspending nanosized solid particles in liquids. Larger thermal conductivity of solid particles compared to the base fluid such as water, ethylene glycol, engine oil, etc. significantly enhances its thermal properties. Numbers of phenomenological models have been proposed to explain the anomalous heat transfer enhancement in nanofluids. This paper presents systematic literature survey observed to exploit several characteristic behaviours of nanofluids viz; increase in thermal conductivity, specific heat and other thermal properties. An empirical correlation for Al2O3 + water and Cu + water nanofluids, and effects of temperature, volume fraction and size of nanoparticle is studied. The effect of temperature on nanofluid thermal conductivity is also brought out. A correlation for the Nusselt number for Al2O3 + water and Cu + water Nanofluids. This behaviour combined with better mechanical properties makes fluids embedded with nanomaterials are excellent candidates for future applications.